2010
DOI: 10.1152/ajplung.00326.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin-deficient mice are protected against tobacco-induced inflammation and increased emphysema

Abstract: Miller M, Pham A, Cho JY, Rosenthal P, Broide DH. Adiponectindeficient mice are protected against tobacco-induced inflammation and increased emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…35) Although several methods 14,[36][37][38][39] have been used to cause COPD or emphysema in animals, the complications seen in human COPD are frequently not found in these experimental COPD animal models or their long term consistency over time has not been determined. Therefore, these animal models are only used in short-term observation and are not suitable for long term research and for clarifying the mechanisms of COPD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35) Although several methods 14,[36][37][38][39] have been used to cause COPD or emphysema in animals, the complications seen in human COPD are frequently not found in these experimental COPD animal models or their long term consistency over time has not been determined. Therefore, these animal models are only used in short-term observation and are not suitable for long term research and for clarifying the mechanisms of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…35,40) In addition to smoking 36,37,41,42) and bacterial infection 43,44) exposure to particulate air pollution, 38,45) occupational dust, smoke 27,46) and bio-fuels for cooking 47) are also risk factors for COPD. Previous experimental COPD or emphysema models have been developed in guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of adiponectin on expression of M2 genes in lung macrophages has not previously been examined, although there is evidence that adiponectin deficiency increases M1 type activation of lung macrophages, as indicated by increased MHC class 2 expression and augmented TNF production [26,27]. However, adiponectin can also have proinflammatory effects on lung macrophages, since macrophages from adiponectin deficient mice produce less TNF in response to cigarette smoke extract than wildtype mice [54].…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al (11) studied the association between adiponectin, interleukin (IL)-6, IL-8 and C-reactive protein with COPD, and found that adiponectin, IL-6 and C-reactive protein were significantly elevated in patients with COPD. Miller et al (12) used an adiponectin null mouse model to study the association between adiponectin and emphysema and observed an increase in diseased animals. Daniele et al (13) used ELISA technique and demonstrated that in patients with COPD, adiponectin levels were significantly upregulated, (14) indicated that in patients with COPD, the anti-inflammatory effect of adiponectin was primarily achieved through inhibiting the activity of macrophages and the release of pro-inflammatory cytokines, such as IL-6 and tumor necrosis factor (TNF)-α, from macrophages.…”
Section: Introductionmentioning
confidence: 99%